PRIORITIES OF PUBLIC ADMINISTRATION IMPROVEMENT IN CIVIL PROTECTION OF TERRITORIAL COMMUNITIES UNDER POWER DECENTRALIZATION IN UKRAINE - Kostenko V.O. (Pressing Problems of Public Administration, 2017)
The paper considers the priority directions of public administration improvement in the  eld of civil protection at the level of associated territorial communities in the process of implementing the local government reform and territorial organization of power in Ukraine. The main tasks of the State Emergency Service of Ukraine in providing assistance to local government bodies in their organization of civil protection measures aimed to ensure a reliable protection of the population and territories from technogenic and natural emergencies are analyzed.